Kejadian Dyspareunia pada Ruptur Perineum: Maria Olva, Sri Astuti dan Maria Magdalena - Poltekkes Kemenkes Bandung (JURNAL RISET KESEHATAN POLTEKKES DEPKES BANDUNG, Online ISSN 2579-8103, 2009)
ABSTRACT Perineal is the important factor on physiology. The intact perineal not only acts on labor but also needed on healthy sexual function. Either factor that connects with trauma perineal on labor is episiotomy or spontaneous rupture. Episiotomy was an operative method that the most used when labor, even though there is a little evidence that support the use. The cause of episiotomy was reported on research that women with episiotomy need a long time to have sexual intercourse. Other researchers found that women with episiotomy would have dyspareunia were about 12-21%. The early work of Master Johnson, Kolodny found that 15 % women have dyspareunia. Spector and Carey reported that incidence of dyspareunia was 8-23%. The objective of the research is to known the correlation of rupture of perineal and dyspareunia and also the factors that influenced it.: the study used cohort design with 53 primipara post labor as respondents which have sexual intercourse 40-60 days after delivery. Technique sampling use purposive sampling. Data are collected by interview with questionnaire for dyspareunia, and examination rupture of perineal when labor. Respondents were interviewed for the second time, to known dyspareunia after sexual intercourse. Analyze data with univariat and bivariat used Fishers Exact Test and cross table 2x2 to determine relative risk. there were 34% women who get dyspareunia. Majority respondent's age was 20-35 years old and education was at senior high school. There wasn't significant correlation between rupture of perineal and dyspareunia (p>0,05), and others influencing factor that include counseling, physical exercise, and lubricant factor.